The The Influence Of Family Motivation, Knowledge Of Profit Sharing Ratio, And Level Of Faith On Interest In Working In Islamic Financial Institutions - Ari Sarwo Indah Safitri; Sri Rahayu Indah Azhary; Idayanti Nursyamsi (Cita konsultindo, 2026)
This study explores the impact of the influence of family motivation, knowledge,’ profit-sharing’ ratio and level of faith on career interests in Islamic institutions. The sample used is students of the faculty’ of economics, the type of research used is quantitative research using primary data types. The results of this study are: family motivation affects work interest, while knowledge of profit sharing ratio and level of faith does not affect student work interest. The next suggestion for researchers is to add samples and focus more on students concentrating on Islamic accounting.